ANALISIS KESULITAN MEMBACA SISWA SEKOLAH DASAR MELALUI ASESMEN MEMBACA PERMULAAN DAN LANJUTAN - Dody Bakhtiar Al-Anshori; Rizki Aningrum (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the forms and causal factors of reading difficulties among elementary school students through the implementation of beginning and advanced reading assessments. The research subjects consisted of three fourth-grade students from SD Isola Bandung who exhibited symptoms of reading difficulties at the frustration level. The study employed a qualitative descriptive approach using observation, interviews, oral reading tests, and reading comprehension tests. The results revealed that all three subjects faced major obstacles in phonological aspects and reading comprehension. The most frequent errors included omission, addition, distortion, and substitution of sounds, as well as neglect of punctuation. The contributing factors to these reading difficulties involved weak phonemic awareness, lack of concentration, and insufficient reading stimulation and guidance from the surrounding environment. These findings highlight the importance of systematic reading assessments to detect reading difficulties at an early stage so that the interventions provided are appropriate and tailored to the individual needs of each student.